An Analysis of the Effectiveness of TikTok Video Content in Increasing Customer Engagement (A Study on Fashion MSMEs in Samarinda) - Eka Yudhyani; Sukirman (LP2M IAIN Palopo, 2025)
This study aims to analyze the most effective TikTok content strategies for fashion Micro, Small, and Medium Enterprises (MSMEs) in Samarinda and to determine the influence of content quality on increasing customer engagement. The research employed a mixed-methods approach, with quantitative data obtained through customer surveys and the analysis of over 100 promotional posts (Code A1-A100) during the April 2025 period. Quantitative analysis utilized Descriptive Statistics and Structural Equation Modeling (SEM), with robust model validation (CFI: 0.925; RMSEA: 0.057). The results of the hypothesis testing indicate that TikTok Video Content has a positive and significant influence on the Increase in Customer Engagement (Standardized Coefficient = 0.684, ). The most effective content is dominated by the principles of Entertainment (highest mean ) and Relatability, with an optimal duration of 15 to 30 seconds. The engagement pattern found tends to be higher in passive and value-marking metrics (Likes and Saves) compared to active metrics (Comments and Shares). Format-wise, Video dominates the awareness metric with the highest Views (Post A44 reached 423,000 Views), while the Carousel format excels in the long-term value (Saves)metric (Post A32 recorded 11,249 Saves). The implications of these findings suggest that MSMEs must focus on duplicating the successful formulas of Video for awareness and Carousel for value, while prioritizing clear Call-to-Actions (CTAs) to boost conversion. However, optimal effectiveness is hindered by major factors such as inconsistent content production and difficulty in mastering the rapid changes in TikTok trends.